The Influence of Organizational Culture, Quality of Human Resources and Work Motivation on Employee Performance at the Tangerang City Environmental Office - Sopiah, Siti; Hadiwijaya, Dudung; Muttaqijijn, M. Imam (International Journal of Science and Society, 2024)
The performance of employees stands as a critical factor determining an organization's success. Strong employee performance plays a pivotal role in enabling an organization to attain its objectives, including enhancements in service quality, productivity, and customer satisfaction. The purpose of this study is to examine the influence of organizational culture, human resource quality, and work motivation on employee performance at the Tangerang City Environmental Agency. This research uses quantitative research methods. Data collection techniques in this study were questionnaires and literature studies. The data in this study were then analyzed using linear regression analysis. The results showed that organizational culture, human resource quality, and work motivation have a positive and significant influence on employee performance both partially and simultaneously. Therefore, these three factors need to be managed properly to improve employee performance.